2006
DOI: 10.1038/sj.bjc.6603171
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of the antiangiogenic peptide ATN-161 (Ac-PHSCN-NH2), a beta integrin antagonist, in patients with solid tumours

Abstract: To evaluate the toxicity, pharmacological and biological properties of ATN-161, a five -amino-acid peptide derived from the synergy region of fibronectin, adult patients with advanced solid tumours were enrolled in eight sequential dose cohorts (0.1 -16 mg kg À1 ), receiving ATN-161 administered as a 10-min infusion thrice weekly. Pharmacokinetic sampling of blood and urine over 7 h was performed on Day 1. Twenty-six patients received from 1 to 14 4-week cycles of treatment. The total number of cycles administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 32 publications
4
109
0
2
Order By: Relevance
“…Although multiple inhibitors of the α 5 β 1 integrin have been shown to be safe in preclinical animal studies, specificity for α 5 β 1 over other RGD-binding integrins remains an elusive target, in part because several of these inhibitors were developed as anticancer agents, in which multi-integrin antagonism has been more effective in animal models of tumor invasion. Nevertheless, the inhibitors currently being used in active clinical trials, including ATN-161, do not have significant reported toxicity (46,47), suggesting that new drugs targeting this pathway could be rapidly moved into clinical trials for intervention in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple inhibitors of the α 5 β 1 integrin have been shown to be safe in preclinical animal studies, specificity for α 5 β 1 over other RGD-binding integrins remains an elusive target, in part because several of these inhibitors were developed as anticancer agents, in which multi-integrin antagonism has been more effective in animal models of tumor invasion. Nevertheless, the inhibitors currently being used in active clinical trials, including ATN-161, do not have significant reported toxicity (46,47), suggesting that new drugs targeting this pathway could be rapidly moved into clinical trials for intervention in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[Jain, 2005]. [Color figure can be viewed in the online version] [Delbaldo et al, 2008;Patel et al, 2001;Posey et al, 2001] Phase II [Beekman et al, 2006;Colevas et al, 2004;Hariharan et al, 2007;MacDonald et al, 2008;Nabors et al, 2007;Raguse et al, 2004] ATN-161 Ac-PHSCN-NH 2 α 5 β 1 , α v β 3 Phase II [Cianfrocca et al, 2006;Donate et al, 2008] …”
Section: Discussionmentioning
confidence: 99%
“…ATN-161 (Ac-PHSCN-NH 2 ) is a mimetic of the fibronectin sequence PHSRN undergoing clinical development for the treatment of solid tumours 170 . It appears to interact with β sub-units, blocking signalling rather than adhesion, and it is thought that this may be due to inhibition of the rearrangement of disulphide bonds necessary for signalling in a similar manner to inhibitors of thiol isomerase action on integrins 164,171 .…”
Section: Receptor Antagonists That Do Not Induce Conformational Changmentioning
confidence: 99%